Interplay of 4f and 3d moments in EuFe2As2 iron pnictides. Issue 1 (4th July 2016) - Maiwald, Jannis; Gegenwart, Philipp
Abstract: EuFe 2 As 2 is unique among 122 iron pnictides due to its 4f magnetic moments. We review its properties with particular emphasis on the interplay between 4f and 3d moments. After discussing the parent compound, we first focus on the evolution of magnetism and superconductivity for hole‐doped Eu 1 − x K x Fe 2 As 2 as well as for chemical and hydrostatic pressure in EuFe 2 (As 1 − x P x ) 2 . Non‐Fermi liquid behavior for optimally doped superconducting systems is highlighted in the electrical resistivity and thermoelectric power. We also discuss the in‐plane anisotropy and how the indirect magnetoelastic coupling between Eu 4f moments and the crystal structure can be used for persistent detwinning of EuFe 2 As 2 in the orthorhombic state by small magnetic fields. Abstract : Iron‐based superconductors feature a rich set of intriguing magnetic, electronic and structural phases. In the case of Eu‐based iron pnictides additional Eu 4 f moments are introduced, that interact with the Fe 3 d moments. In this review, Maiwald and Gegenwart focus on this interplay, which leads to interesting new phases upon chemical doping and application of pressure. The authors also discuss a strong, but indirect magnetoelastic coupling that leads to persistent, structural detwinning.